2007
DOI: 10.1007/s10858-007-9162-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 13Cα chemical shifts for validation of protein structures

Abstract: The 13 C a chemical shifts for 16,299 residues from 213 conformations of four proteins (experimentally determined by X-ray crystallography and Nuclear Magnetic Resonance methods) were computed by using a combination of approaches that includes, but is not limited to, the use of density functional theory. Initially, a validation test of this methodology was carried out by a detailed examination of the correlation between computed and observed 13 C a chemical shifts of 10,564 (of the 16,299) residues from 139 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
112
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(116 citation statements)
references
References 71 publications
(102 reference statements)
4
112
0
Order By: Relevance
“…An analysis in terms of violations of the torsional-angle constraints used during the last step of the structure-determination procedure was carried out for the , , and torsional angles (86 angles) of all of the residues of the Santiveri, Run 1, and Run 2 sets. The selected set of , , and torsional angles belongs to the minimal-rmsd model (2) in which the 13 C ␣ chemical shift of each residue individually best matched the experimental one. This analysis does not consider the torsional angles because the departure of the peptide unit from the planar trans conformation, except for proline, is Ͻ10° (19).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis in terms of violations of the torsional-angle constraints used during the last step of the structure-determination procedure was carried out for the , , and torsional angles (86 angles) of all of the residues of the Santiveri, Run 1, and Run 2 sets. The selected set of , , and torsional angles belongs to the minimal-rmsd model (2) in which the 13 C ␣ chemical shift of each residue individually best matched the experimental one. This analysis does not consider the torsional angles because the departure of the peptide unit from the planar trans conformation, except for proline, is Ͻ10° (19).…”
Section: Resultsmentioning
confidence: 99%
“…This methodology (2), validated on 139 conformations of the human protein ubiquitin, enabled us to offer a new criterion for an accurate assessment of the quality of NMR-derived protein conformations and to examine whether x-ray or NMR-solved structures are better representations of the observed 13 C ␣ chemical shifts in solution. A detailed analysis (2) of the disagreement between observed and density functional theory (DFT)-computed 13 C ␣ chemical shifts in these ubiquitin conformations illustrated the accuracy of the calculations and, more importantly, demonstrated that these disagreements reflect the dynamic nature of the protein rather than inaccuracies of the method. Our methodology has also been used (3) to show that neutral, rather than charged, basic and acidic groups are a better approximation of the observed 13 C ␣ chemical shifts of a protein in solution.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This arbitrary reference was chosen because this physics-based method is extremely sensitive to small conformational changes (10) and, hence, it represent a very accurate (9,36) method with which to computed the 13 C ␣ chemical shifts for a given protein structure model.…”
Section: Internal Standard Referencementioning
confidence: 99%